Immediate Effect of Smart Paraffin Bath Therapy on Leg Pain among Third-Trimester Pregnant Women: A Quasi-Experimental Study - Juneris Aritonang; Surya Anita; Mhd Aldi Primasyukra; Sharfina Haslin; Elisa Silvia Aritonang (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Leg pain is a frequent musculoskeletal complaint among third-trimester pregnant women due to physiological and biomechanics changes during pregnancy. Non-pharmacological pain management approaches are needed during pregnancy because pharmacological options may be limited due to maternal and fetal safety considerations. This study aimed to examine the immediate effect of Smart Paraffin Bath therapy on leg pain intensity among third-trimester pregnant women. Methods: A quasi-experimental study with a non-equivalent control group design was conducted among 28 third-trimester pregnant women with leg pain. Participants were allocated into an intervention group (n = 14) receiving one supervised session of Smart Paraffin Bath therapy and a control group (n = 14) receiving conventional care. Pain intensity was measured using the Visual Analog Scale (VAS) before and immediately after the intervention. Data collection was conducted between May and November 2025. Data were analyzed using paired and independent t-tests. Results: In the intervention group, the mean VAS score decreased from 5.71 ± 0.96 to 4.02 ± 0.88. In the control group, the mean score decreased from 5.91 ± 0.86 to 5.64 ± 0.88, with a mean reduction of 0.27 points (p < 0.001). Pain reduction was greater in the intervention group than in the control group (p < 0.001). Conclusion: Smart Paraffin Bath therapy was associated with an immediate reduction in leg pain intensity among third-trimester pregnant women. However, these findings should be interpreted as preliminary evidence due to small sample size, non-random group allocation, and absence of follow-up assessment.